2011
DOI: 10.1103/physrevb.84.125307
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Aharonov-Bohm effect: Unstrained versus strained type-I semiconductor nanorings

Abstract: The exciton states in strained (In,Ga)As nanorings embedded in a GaAs matrix are computed. The strain distribution is extracted from the continuum mechanical model, and the exact diagonalization approach is employed to compute the exciton states. Weak oscillations of the ground exciton state energy with the magnetic field normal to the ring are an expression of the excitonic Aharonov-Bohm effect. Those oscillations arise from anticrossings between the ground and the second exciton state and can be enhanced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
1
19
0
2
Order By: Relevance
“…1. For k z beyond the X point the dispersion relations of all bands should be mirror symmetric to the dispersion relations left of the X point, 34,35 such as the ones shown by the dashed lines in Fig. 1.…”
Section: The Bulk Band Structure Of Siliconmentioning
confidence: 89%
“…1. For k z beyond the X point the dispersion relations of all bands should be mirror symmetric to the dispersion relations left of the X point, 34,35 such as the ones shown by the dashed lines in Fig. 1.…”
Section: The Bulk Band Structure Of Siliconmentioning
confidence: 89%
“…12-17) have stimulated theoretical and experimental studies of the AB oscillations in the persistent currents carried by single-and few-particle states (see, e.g., Refs. [18][19][20][21][22][23][24]. Using an ultrasensitive torsion magnetometer, AB oscillations in the magnetic moment of In x Ga 1−x As self-assembled quantum rings have been observed 18 with a magnitude of oscillation as large as 60% to 70% of the corresponding magnitude in an ideal ring.…”
Section: Introductionmentioning
confidence: 98%
“…In our recent work, we modeled excitons in 3D GaAs/(Al,Ga)As and (In,Ga)As/GaAs nanorings [5], and found that EAB oscillations can appear in the exciton ground energy level. Furthermore, strain in the (In,Ga)As/GaAs nanoring leads to a spatial separation of the electron and the hole like in a type-II quantum dot, which increases the exciton polarization.…”
mentioning
confidence: 99%